1994
DOI: 10.1111/j.1423-0410.1994.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Transfusion Errors

Abstract: The true incidence of bedside transfusion errors, i.e. those happening when blood products have left the blood bank, is underestimated because published figures rely on reporting of clinically relevant events or on indirect methods. The SAnGUIS project assessing blood practice in a prospective and randomized fashion for 6 elective surgical procedures gave the opportunity to trace all transfused units and to identify steps at risk during blood delivery in surgery. We considered transfusion of a wrong unit as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Only 25% (7 out of 28) of transfusion errors resulted in mistransfusion, whereas 75% were averted, having been detected as near misses. Even this is probably an underestimate of the true number of events because errors outside the ABO blood group system (ABO-compatible errors) are less likely to be detected, sought after (Lumadue et al, 1997) or, as reported by the Belgian SANGUIS Group, a retrospective analysis is more likely to underestimate the number of errors as it relies on voluntary reporting of errors rather than the systematic approach to error detection, as in the case of prospective study (Baele et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Only 25% (7 out of 28) of transfusion errors resulted in mistransfusion, whereas 75% were averted, having been detected as near misses. Even this is probably an underestimate of the true number of events because errors outside the ABO blood group system (ABO-compatible errors) are less likely to be detected, sought after (Lumadue et al, 1997) or, as reported by the Belgian SANGUIS Group, a retrospective analysis is more likely to underestimate the number of errors as it relies on voluntary reporting of errors rather than the systematic approach to error detection, as in the case of prospective study (Baele et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Baele et al reported bedside transfusion errors occur in 12.4/ 1000 transfusions. 10 Goodnough estimated that the administrative errors were the most serious risks leading to Acute ABO incompatible hemolytic reactions. 11 Overall risk of acute hemolytic reactions in present study was 0.32 per thousand transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Some efforts have been made to scale measurements of noninfectious transfusion-related events, including MERS-TM,[2] the voluntary program SHOT,[4] the mandatory transfusion-related incidents/accidents/medical errors reporting system of the New York State Department of Health,[5] the French Haemovigilance System,[6] and Belgium's SANGUIS Group. [7] Near-miss events were estimated to be five times that of the actual events. [8] Although the hemovigilance system managed by the Red Cross is being demonstrated and executed as the primary reporting system, it cannot be established as a complete hemovigilance system without relationships to hospital blood banks.…”
Section: Introductionmentioning
confidence: 99%